Radiation-Induced Painful Neurogenic Hypertrophy Treated With Botulinum Toxin A. Issue 3 (March 2018) - Filippakis, Alexandra; Ho, Doreen T.; Small, Juan E.; Small, Kirstin M.; Ensrud, Erik R.
Abstract : Abstract: Painful neurogenic hypertrophy is a rare complication of radiation therapy. We report a 27-year-old woman with a history of adenoid cystic carcinoma of the submandibular gland presented with painful twitching of her left shoulder. Electrodiagnostic studies were consistent with a diagnosis of radiation-induced spinal accessory nerve hyperactivity. The patient failed conventional medical therapy. She was treated with an injection of botulinum toxin A, and within 1 month experienced significant relief of symptoms. We thus conclude that Botulinum toxin is a therapeutic option for the pain associated with radiation-induced peripheral nerve hyperactivity.